Enhancing critical thinking skills through the integration of problem-based learning and flipped learning - Muhammad Yani (Jurnal Inovasi Guru Indonesia, 2026)
Background: The rapid integration of digital technology in education has intensified the need for instructional models that effectively foster higher-order thinking skills. Critical thinking has emerged as a fundamental competency in contemporary curricula; however, conventional teacher-centered approaches often provide limited opportunities for structured inquiry and analytical reasoning. The integration of Problem-Based Learning (PBL) and Flipped Learning offers a promising framework that aligns pre-class digital preparation with in-class collaborative problem solving. Objective: This study aimed to examine the effectiveness of integrating Problem-Based Learning and Flipped Learning in enhancing students’ critical thinking skills in secondary education. Methods: A quasi-experimental design with a non-equivalent control group pretest–posttest structure was employed. Sixty-four students were assigned to experimental and control groups. The experimental group received instruction through an integrated PBL–Flipped Learning model for eight sessions, while the control group received conventional instruction. Critical thinking skills were measured using a validated test covering analysis, interpretation, inference, explanation, and evaluation indicators. Data were analyzed using paired and independent samples t-tests, and effect size was calculated using Cohen’s d. Results: The findings revealed a statistically significant improvement in critical thinking skills in both groups; however, the experimental group demonstrated substantially higher posttest scores and a large effect size compared to the control group. The integration model effectively enhanced analytical reasoning, collaborative argumentation, and reflective evaluation during structured problem-solving activities. Conclusion: The integration of Problem-Based Learning and Flipped Learning significantly enhances students’ critical thinking skills by providing systematic pre-class preparation and inquiry-based in-class engagement. The model offers a robust instructional framework for promoting higher-order cognitive development in secondary education.